Фільтрація вхідної інформації в підсистемах технологічного моніторингу систем керування цукровим виробництвом - Кишенько, В. Д.; Проскурка, Є. С. (Eastern-European Journal of Enterprise Technologies, 2009)
The considered questions that connected with the analysis and preparation of the entrance information received under production conditions of food manufactures, in particular, in sugar manufactures, for the organisation of effective actions in control systems of technological processes. These problems are carried out within the limits of subsystems of technological monitoring which provides an establishment of situationally meaning events according to management scenarios. The problem of a filtration of time numbers on the basis of wavelet-transformations and methods of nonlinear dynamics and chaos dares